White Mangrove Pidada (Sonneratia Alba) Leaves Extract in Handbody Lotions: A Qualitative Evaluation and Alignment With Indonesian National Standards - Nisa, Husna Idza Auziadzatun; Pambudi, Dwi Bagus; Mugiyanto, Eko (Universitas Muhammadiyah Surakarta, 2024)
The White Mangrove Pidada Leaves (Sonneratia alba) serve as a source of secondary metabolites, including phenols, tannins, steroids, and flavonoids, known for their high antioxidant content, making them effective in countering free radicals. The choice of a handbody lotion formulation is based on its easy skin absorption, non-sticky nature, and absence of residue upon application. The focus of this study is to evaluate the handbody lotion formulation enriched with White Mangrove Pidada Leaves extract. Utilizing a qualitative approach, this study employed a cycling test conducted over three cycles for the evaluation of handbody lotion formulations. After three cycles, Formula A demonstrated a semi-solid consistency, light green color with a grape scent, pH 6, and homogeneity. Notably, it showcased a spreadability of 4.925 cm, adhesiveness of 1.76 seconds, and viscosity of 6.791 mPa.S. In the case of Formula B, a semi-solid with a light green color and grape scent, despite having pH 6, exhibited a lack of homogeneity, with a spreadability of 5.175 cm, adhesiveness of 1.37 seconds, and viscosity of 6.592 mPa.S. Formula C, characterized as a semi-solid with a dark green color and grape scent, displayed homogeneity, pH 6, a spreadability of 5.25 cm, adhesiveness of 2 seconds, and viscosity of 7.568 mPa.S. The findings lead to the conclusion that, following three cycles, the handbody lotion formulations align with the criteria established by the Indonesian National Standard (SNI).